Goal Oriented Evaluation Using the Delphi Method in Implementing Teaching Factory Multimedia - Lisna Nurrohmawati; Yuliatri Sastrawijaya; Efri Sandi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
Contextual vocational education makes students able to link the skills acquired with their application in the real world so they will have appropriate competencies. Learning with teaching factory has a focus point, namely the application of competency-based learning patterns supported by production-based learning with link and match between vocational high schools and industry. This research was a mixed method research. This study used the goal oriented program evaluation model with Delphi method to obtain the opinion of experts to determine the standard of assessment that has been used to measure the implementation of teaching factory. The Delphi method used panelist discussions of experts from the multimedia industry and national teaching factory sources. The goal oriented evaluation model was used to measure program achievement based on the objectives of the teaching factory program applied to the Sekolah Menengah Kejuruan (SMK) level. The research was conducted at SMK that hold multimedia expertise competencies in Bogor Regency. The types of research instruments used were observation, interviews, and questionnaires. Validity test with Lawshe technique and reliability test using Chronbach Alpha. The research sample consisted of eleven schools with an average overall result in Bogor Regency was 82.23. Based on these values, it can be concluded that the implementation of the teaching factory in Bogor Regency is well implemented.